Parents' education and children's outcomes: is the gradient getting steeper? - Redmond, G; Smart, D; Katz, I; Gubhaju, B (My University, 2010)
This paper compares the relationship between parents' education and children's outcomes in two surveys that follow Australian cohorts of children through their early years - the Australian Temperament Project (following children born in Victoria in the early 1980s) and the Longitudinal Study of Australian Children (following children born in 1999). Over this period there has been a revolution in education in Australia. In the early 1980s, relatively few parents had a tertiary education, and a large proportion left school without qualifications. In the 2000s, a high proportion of parents have at least a bachelor degree (and significant numbers have higher qualifications), and very few leave school without any qualifications. This paper finds that the relationship between parental education and children's behavioural problems has grown more acute over the years: a low level of parental education is a stronger determinant of children's behavioural outcomes around age 9 now than 20 years previously. On the other hand, the association between parents' education and children's verbal reasoning/reading skills appears to have changed little. The paper explores how other factors, such as the child's temperament, and sociop-demographic factors including gender and ethnic background may mediate these relationships between parental education and child outcomes in the early 1980s and 20 years later.
Keywords: Children; Children -- Outcomes; Childhood and child development; Children; Outcomes; Childhood and child development